Investigating the interrelationship between rated L2 proficiency and linguistic complexity in L2 speech. (July 2020) - Bulté, Bram; Roothooft, Hanne
Abstract: This study investigates the relationship between nine quantitative measures of L2 speech complexity and subjectively rated L2 proficiency by comparing the oral productions of English L2 learners at five IELTS proficiency levels. We carry out ANOVAs with pairwise comparisons to identify differences between proficiency levels, as well as ordinal logistic regression modelling, allowing us to combine multiple complexity dimensions in a single analysis. The results show that for eight out of nine measures, targeting syntactic, lexical and morphological complexity, a significant overall effect of proficiency level was found, with measures of lexical diversity (i.e. Guiraud's index and HD-D), overall syntactic complexity (mean length of AS-unit), phrasal elaboration (mean length of noun phrase) and morphological richness (morphological complexity index) showing the strongest association with proficiency level. Three complexity measures emerged as significant predictors in our logistic regression model, each targeting different linguistic dimensions: Guiraud's index, the subordination ratio and the morphological complexity index.